PEMBELAJARAN BERBASIS MASALAH DALAM MENGEMBANGKAN BERPIKIR KRITIS DAN KREATIF SISWA UNTUK MEWUJUDKAN PROFIL PELAJAR PANCASILA - Riska; Riska, Riska; Dwi Puspita, Ryan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This study aims to improve the critical and creative thinking skills of elementary school students through the application of the Problem-Based Learning (PBL) model. The background of this research is the low level of students' higher-order thinking skills, due to the dominance of conventional teaching methods that fail to actively involve students in the learning process. The research employed a Classroom Action Research (CAR) design, implemented in two cycles, with each cycle consisting of four stages: planning, action, observation, and reflection. The population in this study was fifth-grade students of an elementary school in Indonesia. The sample was selected using a purposive sampling technique, involving one class of 28 students. The research was conducted over two months, from February to March 2025, at SD Negeri Kutai, Indonesia. Data collection techniques included tests of critical thinking, student activity observation sheets, and creativity questionnaires. The research instruments consisted of a critical thinking test, a student activity observation sheet, and a creativity questionnaire. The data were analyzed using descriptive and comparative techniques between cycles to measure improvements in students’ thinking skills and learning activities. The results showed that the application of PBL significantly improved students’ critical and creative thinking abilities, as indicated by increased test scores, more active participation in learning activities, and higher creativity scores in each cycle. In addition, this model also supported the strengthening of Pancasila Student Profile values, such as collaboration, responsibility, and environmental awareness. Based on these findings, it can be concluded that Problem-Based Learning is an effective instructional method to foster students’ character development and 21st-century skills in elementary education